The Social Context of Driving Cessation: Understanding the Effects of Cessation on the Life Satisfaction of Older Drivers and Their Social Partners. (December 2019) - Schryer, Emily; Boerner, Kathrin; Horowitz, Amy; Reinhardt, Joann P.; Mock, Steven E.
Older adults with vision loss and a friend or family member were interviewed over a 2-year period. We examined the effects of driving cessation on life satisfaction among older adults and a social contact. Drivers' use of public transportation was examined as a moderator. Driving cessation was associated with a decline in life satisfaction among social partners but not for the drivers. Drivers' use of public transportation at baseline moderated the effects of cessation on changes in well-being among social partners, but had little effect on the life satisfaction of the drivers. Life satisfaction was greater among the social partners of ex-drivers who used public transportation more frequently. The association between driving cessation and well-being should be studied in the context of older drivers' social networks. Infrastructure (e.g., subways and buses) that supports transportation needs plays an important role in mitigating the effects of cessation on older adults' social networks.